2014
DOI: 10.1175/bams-d-12-00050.1
|View full text |Cite
|
Sign up to set email alerts
|

The North American Multimodel Ensemble: Phase-1 Seasonal-to-Interannual Prediction; Phase-2 toward Developing Intraseasonal Prediction

Abstract: The North American Multimodel Ensemble prediction experiment is described, and forecast quality and methods for accessing digital and graphical data from the model are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
747
0
3

Year Published

2014
2014
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 836 publications
(765 citation statements)
references
References 32 publications
15
747
0
3
Order By: Relevance
“…2, left panel). This behavior is explained by the fact that CCSM4 shares initial conditions with CFSv2 (Kirtman et al 2014;Infanti and Kirtman 2016), which come from the Climate Forecast System Reanalysis (CFSR; Saha et al 2010).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…2, left panel). This behavior is explained by the fact that CCSM4 shares initial conditions with CFSv2 (Kirtman et al 2014;Infanti and Kirtman 2016), which come from the Climate Forecast System Reanalysis (CFSR; Saha et al 2010).…”
Section: Methodsmentioning
confidence: 99%
“…The models are those of the North American Multi-model ensemble (NMME; Kirtman et al 2014), and include models from both operational forecast producing centers and research institutions in the U.S. and Canada. This model set contains some, but not all, of today's leading state-of-the-science models.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Formatconsistent data and output from numerous ensemble members from eight North American GCMs are archived. (For further details about NMME models, see Kirtman et al, 2014).…”
Section: Winter Forecasts Based On El Niñomentioning
confidence: 99%
“…In this study, we mainly consider the effect of model biases and how MME may improve the simulations. MME has been applied to both coupled earth system models (Krishnamurti et al 2000;Barnston et al 2003;Palmer et al 2004;Kirtman et al 2014) and offline LSMs (Guo et al 2007), and it was found that results from MME are generally better than those from most individual models. An unexplored problem is whether a land model ensemble can improve climate simulations in coupled land-atmosphere models and how effective the land model ensemble is compared to the traditional MME across the coupled models.…”
Section: Introductionmentioning
confidence: 99%